Physical Modeling and Numerical Simulation of the Seismic Responses of Metro Tunnel near Active Ground Fissures - Nina Liu; Quanzhong Lu; Jun Li; Jianbing Peng; Wen Fan; Weiliang Liu (Complexity)
Ground fissures pose serious hazards to underground, as well as aboveground, structures. In underground railways, which are near ground fissures, the potential for disasters is even higher since tunnels face threats from fissure activities. To determine the interaction between a tunnel and ground fissure in the event of an earthquake, field surveys and data analysis were applied to study the activity and damage caused by the fissure. Shaking table tests and a numerical simulation model were used to understand the dynamic response of the fissure site and tunnel. The fissure site had a clear hanging wall effect, where the acceleration amplification was larger in the hanging wall than that in the footwall both on the surface and at the middle of the fissure site. The zone of influence was also wider in the hanging wall. The acceleration magnification factor increased with the burial depth and peak acceleration of the input earthquake. The peak ground acceleration (PGA) decreased with the burial depth on both sides of the fissure. The greatest PGA coefficient was obtained at the surface of the site. The vertical soil pressure was influenced by the metro tunnel and fissure. The vertical soil pressure was larger in the hanging wall, especially in the zone near the fissure, but was less near the tunnel. The horizontal soil pressure above the tunnel was less than that near the fissure. The results of this study are essential for the safe design of underground railway systems.